Vitale democratie Theorie van democratie in actie - Hendriks, Frank (Studies over politieke vernieuwing, 2006)
Democracy is one of the most used and misinterpreted terms of our time. In public discussions concerning the subject it is tacitly assumed that everyone is aware of the meaning of democracy and the implications it carries. In reality democratic ideals and practices take on various forms in various countries. Frank Hendriks sheds light on this subject matter in a comprehensible manner. He distinguishes four ground forms of democracy, which are inherent to democratic forms everywhere. Along with "consensus democracy", Hendriks compares "pendulum democracy", "voter democracy" and "participatory democracy", at national as well as subnational levels of governance. Hendriks concludes in his studies that contrary to popular belief, not one model is superior to the others and calls for a realistic approach to a democracy that is sensitive to the context in which democracy must prove and sustain itself.